2021
DOI: 10.1111/nph.17186
|View full text |Cite
|
Sign up to set email alerts
|

Born with a silver spoon: dandelion parents’ life experiences affect the lives and afterlives of their offspring

Abstract: This article is a Commentary on Puy et al. (2021), 229: 3497–3507.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…In summary, we found that long‐term simulated climate warming and N deposition elicited adaptive maternal effects and that offspring environments strongly influenced its performance, thereby supporting the hypothesis that perennial plants have the capacity to inherit adaptive plasticity (van Moorsel, 2021) but decline the hypothesis that perennial plants lack adaptive maternal effects (Uller et al., 2013; Yin et al., 2019). In this study, we focused exclusively on maternal effects and did not consider paternal effects.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In summary, we found that long‐term simulated climate warming and N deposition elicited adaptive maternal effects and that offspring environments strongly influenced its performance, thereby supporting the hypothesis that perennial plants have the capacity to inherit adaptive plasticity (van Moorsel, 2021) but decline the hypothesis that perennial plants lack adaptive maternal effects (Uller et al., 2013; Yin et al., 2019). In this study, we focused exclusively on maternal effects and did not consider paternal effects.…”
Section: Discussionsupporting
confidence: 73%
“…The majority of previous studies have considered two different states of an environmental variable or two different environments (Donelson et al., 2018). Thus, it is necessary to conduct multiple‐factor studies to better understand the relative importance of different factors or environmental matches in maternal effects (Fenesi et al., 2014; van Moorsel, 2021). Climate warming can alter thermal regimes and N deposition can alter soil N availability, and thus these two global changes are particularly relevant to maternal effects (Donelson et al., 2018; Herman & Sultan, 2011; Lau et al., 2008; van Moorsel, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations